Mathematical Investigation of Cryptographic Functions and Operations Used in Cyber Attacks - Gencoglu, Muharrem Tuncay (Ieee, 2017)
Cryptography has always been a corner stone of security domain. Different security services such as confidentiality, integrity, availability, authentication, non repudiation and access control, are provided by a number of cryptographic algorithms including block ciphers, stream ciphers and hash functions. Until to day, different operations and functions used in cryptography. In this paper, I have as mathematical survey of cryptographic functions and operations of the algorithms used in cyher attacks. Then, time series analysis of used algorithms have perform and their fruquency of use have determined. This investigation will help for identifying different operations and functions in cryptographic algorithms.
2017 International Conference on Computer Science and Engineering (UBMK) -- OCT 05-08, 2017 -- Antalya, TURKEY
Keywords: Algorithms; Cipher; Clyptanalysis; Functions; Cyber Attacks